USE OF SCIENTIFIC AND LEGAL RESEARCH IN JUDICIAL PRACTICE:PROBLEMS, CURRENT EXPERIENCE AND PROSPECTS (Universal International Scientific Journal, 2026)
This article examines the issues of using scientific and legal research in judicial practice. It also identifies problems encountered in the process of using scientific research in judicial practice and analyzes the reasons for their occurrence based on scientific and regulatory and legal sources.
Keywords: court; court practice; research